Target markets: international terrorism meets global capitalism in the mall - Mirgani, Suzi (Culture & theory, 2017)
This ground-breaking book explores the points of convergence between corporate capitalism and terrorist practice. Assessing the increase in the number of terrorist attacks directed against commercial entities in urban areas, such as the Westgate mall in Nairobi or the Charlie Hebdo offices in Paris, Suzi Mirgani offers a fascinating and disturbing perspective on the spaces where supposedly oppositional ends of the spectrum meet on common ground. How is it that these urban commercial spaces provide ground zero for a conference between the most powerful forces of contemporary culture: the most mainstream and the most extreme?